2019
DOI: 10.1097/prs.0000000000005219
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Factors for Hearing Outcomes in Children with Cleft Lip and Palate

Abstract: Background: This study was performed to investigate the prognostic factors that influence hearing outcomes of children with cleft lip and palate after ventilation tube insertion. Methods: The authors retrospectively reviewed the hearing thresholds of 90 children with cleft lip and palate and performed univariate and multivariate analyses of five prognostic factors for hearing outcomes: age at palatoplasty, age at first ventilation tube insertion, timing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 22 publications
0
29
0
Order By: Relevance
“…Kim et al (2017) investigated hearing outcomes between children with their first tympanostomy tubes placed before and after 8 years of age and found no statistically significant difference in outcomes. Another study compared intervention before and after 1 year of age and did find better hearing outcomes with earlier intervention, but this association disappeared upon multivariate analysis (Yang et al, 2019). Conversely, Hubbard et al (1985) reported superior hearing outcomes in a cohort of patients with tympanostomy tubes inserted at an average age of 3 months compared to 30 months.…”
Section: Discussionmentioning
confidence: 99%
“…Kim et al (2017) investigated hearing outcomes between children with their first tympanostomy tubes placed before and after 8 years of age and found no statistically significant difference in outcomes. Another study compared intervention before and after 1 year of age and did find better hearing outcomes with earlier intervention, but this association disappeared upon multivariate analysis (Yang et al, 2019). Conversely, Hubbard et al (1985) reported superior hearing outcomes in a cohort of patients with tympanostomy tubes inserted at an average age of 3 months compared to 30 months.…”
Section: Discussionmentioning
confidence: 99%
“…13 In current literature, different approaches are presented for the treatment of patients with cleft palate and with conductive hearing loss due to effusion in the tympanic cavity. [14][15][16][17] Paracentesis and tympanostomy tube surgery (TTS) are the main treatment options for correcting middle ear dysfunction. This study evaluates the prevalence of tympanostomy tube placement in patients with cleft deformities in relation to the absolute and relative cleft width and cleft classification.…”
Section: Introductionmentioning
confidence: 99%
“…As with the literature regarding maxillofacial growth, several considerations complicate the interpretation of the literature examining the impact of timing of palatoplasty on speech and language outcomes. First, variability in criteria used to define “early” and “late” palatoplasty exists, with early age for simultaneous soft and hard palate repair ranging from 3 months (Kaplan, 1981) to 6 months (Ysunza et al, 1998; Kirschner et al, 2000) to 24 months (Yang et al, 2013), and late age ranging from >12 months (Randall et al, 1986; Yang et al, 2019) to >18 months (Pasick et al, 2014) to >2 years (Zhao et al, 2012; Guneren et al, 2015; Carlson et al, 2016; Menegueti et al, 2017), depending on the study. Further variability is introduced by studies examining staged closure of the soft and hard palate (Cosman and Falk, 1980; Randall et al, 1983; Kirschner et al, 2000; Holland et al, 2007; Yamanishi et al, 2011).…”
Section: Introductionmentioning
confidence: 99%